Efficient Suppression of Chain Transfer and Branching via Cs‐Type Shielding in a Neutral Nickel(II) Catalyst. (23rd December 2020) - Wang, Chaoqun; Kang, Xiaohui; Dai, Shengyu; Cui, Fengchao; Li, Yunqi; Mu, Hongliang; Mecking, Stefan; Jian, Zhongbao
Abstract: An effective shielding of both apical positions of a neutral Ni II active site is achieved by dibenzosuberyl groups, both attached via the same donors' N ‐aryl group in a C s ‐type arrangement. The key aniline building block is accessible in a single step from commercially available dibenzosuberol. This shielding approach suppresses chain transfer and branch formation to such an extent that ultrahigh molecular weight polyethylenes (5×10 6  g mol −1 ) are accessible, with a strictly linear microstructure (<0.1 branches/1000C). Key features of this highly active (4.3×10 5  turnovers h −1 ) catalyst are an exceptionally facile preparation, thermal robustness (up to 90 °C polymerization temperature), ability for living polymerization and compatibility with THF as a polar reaction medium. Abstract : The β‐H elimination event that brings about chain transfer and branch formation in neutral nickel‐catalyzed olefin insertion polymerization is now fully addressed by a C s ‐type shielding of both apical positions of a neutral Ni II catalyst. Thus, strictly linear (<0.1 brs/1000C) ultrahigh molecular weight polyethylenes (UHMWPEs; 5050 kDa) are now accessible.